2009
DOI: 10.1063/1.3260233
|View full text |Cite
|
Sign up to set email alerts
|

Auto-oscillation and narrow spectral lines in spin-torque oscillators based on MgO magnetic tunnel junctions

Abstract: We demonstrate spin-torque induced coherent auto-oscillation in magnetic tunnel junctions of composition PtMn/CoFe/Ru/CoFeB/MgO/CoFeB and of low resistance-area product. At the generation threshold, we observe a strong line narrowing down to 6 MHz at 300 K and a dramatic increase in oscillator power, yielding spectrally pure oscillations with extremely low flicker noise. The induced auto-oscillations are observed even at zero applied field. The frequency of the oscillation mode, and its dependence with easy an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The large majority of reported results rely in MTJs where the MTJ transport properties are dominated by defects. These defects are present already on the as-deposited state 29 or, in some cases, are created prior to the dynamic characterization of the system by applying large currents that irreversibly change the transport properties of the device in a non-controlled way, which is required in order to observe STT persistent oscillations 36 . The effect of such defects on the dynamics is still not well accounted and, on top of that, the higher TMR and resistance of thicker MgO barriers should increase P out .…”
Section: Introductionmentioning
confidence: 99%
“…The large majority of reported results rely in MTJs where the MTJ transport properties are dominated by defects. These defects are present already on the as-deposited state 29 or, in some cases, are created prior to the dynamic characterization of the system by applying large currents that irreversibly change the transport properties of the device in a non-controlled way, which is required in order to observe STT persistent oscillations 36 . The effect of such defects on the dynamics is still not well accounted and, on top of that, the higher TMR and resistance of thicker MgO barriers should increase P out .…”
Section: Introductionmentioning
confidence: 99%
“…Second, nanoscale microwave emitting systems are of a large practical interest, allowing in principle the creation of generators with the sizes less than 1 mkm for the wide frequency regions (from several tens of MHz to several hundreds of GHz), which frequency could be tuned simply by changing the dc current strength. For this reasons a very large effort has been applied for experimental studies of these microwave oscillators, with the aim to the decrease the oscillator linewidth and to achieve the largest possible microwave emission power [16,17,18,19,20,21,22]. Although a substantial progress could be achieved in both directions, corresponding parameters of a single oscillator are still not good enough for potential applications (including detection of radio frequency magnetic fields and telecommunication).…”
Section: Introductionmentioning
confidence: 99%
“…78 In general, the linewidth of STNOs strongly depends on both device geometry and materials and the operation conditions. The linewidth for a single nano-contact device can vary from a few MHz to 100 MHz as the current and applied magnetic fields are varied, 14,20,25,79 while linewidths for nano-pillars can vary from several tens MHz 22,58,59,61,75,76 to the GHz level. 12,23,60,61,64 One of remaining challenges in the STNO design is the achievement of a narrow linewidth and a large output power at the same time in order to utilize them for practical applications.…”
Section: Linewidthmentioning
confidence: 99%
“…Very recently, our works 22,26 demonstrated that the I c value can be significantly reduced by introducing the IPA the free layer, which can partially cancel the effect of the demagnetizing field. [71][72][73][74] The STNO utilizing perpendicular anisotropy exhibits simultaneously highest output power 0.28 µW (> 0.95 µW if delivered to the matched load) and a linewidth smaller than 25 MHz (comparable to that of LTMR STNOs 75,76 ) in the same device, as well as the suppression of the secondary oscillation modes. Fig.…”
Section: Output Powermentioning
confidence: 99%